A Comparative Study on the Behavior of Steel Moment-Resisting Frames with Different Bracing Systems Based on a Response-Based Damage Index - Kamran Karsaz; Seyed Vahid Razavi Tosee (Salehan Institute of Higher Education, 2018)
Seismic rehabilitation of existing buildings is one of the most effective ways to reduce damages under destructive earthquakes. The use of bracings is one of techniques for seismic rehabilitation of steel structures. In this study we aimed to investigate the seismic performance of three 5, 10 and 15-storey steel structures with moment-resisting frames designed three dimensionally in ETABS 2015 application based on first edition of Iranian Standard 2800. Their damage under five ground motions was evaluated using response-based damage model proposed by Ghobara et al. (1999). Then, the structures were rehabilitated with different bracing systems (X, eccentric and concentric V and inverted-V) and, again, their damage under five earthquakes were evaluated and compared with those of moment resisting frames. The pushover analysis results indicated that X-braced frame was the least ductile system but had highest initial stiffness and yield stress. In low-rise building, X-braced frames showed better performance among studied bracing systems compared to moment resisting frames, while mid and high-rise buildings with eccentrically braced frame (EBF) showed the best behavior against earthquakes with the least damage. Moreover, it was found out that EBFs’ performance increases by increasing storey height, but for concentrically braced frames (CBFs) it was decreased. We concluded that the use of response-based damage models can be a suitable procedure for estimating the vulnerability of steel structures rehabilitated with bracing system.